Challenges during Electroconvulsive Therapy—A Review - Bansal, Sonia; Surve, Rohini M.; Dayananda, Rajeev (Journal of Neuroanaesthesiology and Critical Care, 2021)
Electroconvulsive therapy (ECT) is one of the most successful treatment techniques employed in psychiatric practice. ECT is usually administered as a last resort to a patient who fails to respond to medical management or on an urgent basis as a life-saving procedure when immediate response is desired. It is performed under general anesthesia and is often associated with autonomic changes. All attempts should be made to minimize the resulting hemodynamic disturbances in all the patients using various pharmacological methods. Anesthesiologists providing anesthesia for ECT frequently encounter patients with diverse risk factors. Concurrent cardiovascular, neurological, respiratory, and endocrine disorders may require modification of anesthetic technique. It is ideal to optimize patients before ECT. In this review, the authors discuss the optimization, management, and modification of anesthesia care for patients with various cardiac, neurological, respiratory, and endocrine disorders presenting for ECT to improve the safety of the procedure. It is not infrequent that an anesthesiologist also plays an important role in inducing a seizure. Proconvulsants such as caffeine, adjuvants like opioids, hyperventilation, and appropriate choice of anesthetic agent for induction such as etomidate or ketamine can help. The use of BIS monitoring to guide the timing of electric stimulation is also elaborated in this review.
Keywords: anesthesia; electroconvulsive therapy; challenges; concurrent diseases; proconvulsant; systemic diseases